Multiple Poses and Thermodynamics of Ligands Targeting Protein Surfaces: The Case of Furosemide Binding to mitoNEET in Aqueous Solution - Hoang, Linh Gia; Goßen, Jonas; Capelli, Riccardo; Nguyen, Toan T.; Sun, Zhaoxi; Zuo, Ke; Schulz, Jörg B.; Rossetti, Giulia; Carloni, Paolo (Frontiers in Cell and Developmental Biology, 2022)
Human NEET proteins, such as NAF-1 and mitoNEET, are homodimeric, redox iron-sulfur proteins characterized by triple cysteine and one histidines-coordinated [2Fe-2S] cluster. They exist in an oxidized and reduced state. Abnormal release of the latter is implicated in a variety of diseases, including cancer and neurodegeneration. The computer-aided and structure-based design of ligands affecting cluster release is of paramount importance from a pharmaceutical perspective. Unfortunately, experimental structural information so far is limited to only one ligand/protein complex. This is the X-ray structure of furosemide bound to oxidized mitoNEET. Here we employ an enhanced sampling approach, Localized Volume-based Metadynamics, developed by some of us, to identify binding poses of furosemide binding to human mitoNEET protein in solution. The binding modes show a high variability within the same shallow binding pocket on the protein surface identified in the X-ray structure. Among the different binding conformations, one of them is in agreement with that found in the crystal structure. This conformation might have been selected in the latter because of the presence of crystal packing interactions, absent in solution. The calculated binding affinity is compatible with experimental data, with the caveat that the latter may be affected by cluster release during the in vitro measurements, shown in previous studies. Our protocol can be used in a straightforward manner in drug design campaigns targeting this pharmaceutically important family of proteins.